Case Report of Floating-Harbor Syndrome With Bilateral Cleft Lip. (January 2020) - Ko, Jaemin; Pomerantz, Jason H.; Perry, Hazel; Shieh, Joseph T.; Slavotinek, Anne M.; Oberoi, Snehlata; Klein, Ophir D.
Floating-Harbor syndrome (FHS) is a rare genetic disorder caused by heterozygous mutations in the Snf2-related CREBBP activator protein ( SRCAP ) gene. The syndrome is characterized by proportional short stature, delayed bone maturation, delayed speech development, and facial dysmorphism. Submucous cleft palate and cleft lip have been reported in FHS, but to our knowledge orofacial clefting in this condition has not been assessed in detail. Here, we report on a case of bilateral cleft lip in a patient with FHS confirmed by exome sequencing.